Critical health education studies: Reflections on a new conference and this themed symposium. (October 2019) - Fitzpatrick, Katie; Leahy, Deana; Webber, Melinda; Gilbert, Jen; Lupton, Deborah; Aggleton, Peter
In May 2018, a group of scholars gathered in the icy and sunlit grandeur of Queenstown (Aotearoa New Zealand) to talk, debate and share ideas about health education. The conference aimed to trouble and disrupt traditional kinds of health education and, instead, suggest possibilities for the critical study of health education – both in terms of theory and practice. This introduction to the special themed symposium is a reflection by the six authors on that new conference – Critical Studies in Health Education (CHESS) – and what it aimed to achieve. The authors discuss and define the intent of critical approaches to health education, and reflect on their experiences of the conference, as well as the future of the field. Papers in this special themed symposium of Health Education Journal are also introduced.